DASAR PENGENAAN SANKSI PIDANA PENJARA TERHADAP PENYALAHGUNA NARKOTIKA BAGI DIRI SENDIRI (STUDI PUTUSAN Nomor 408/Pid.Sus/2019/PN.Bil.) - Christina, Maria (Universitas Negeri Surabaya, 2020)
The judge in imposing a criminal case against narcotic must pay attention to the Law Number 35 Year 2009 on Narcotics and its derivatives rules. At the stage a ruling in the tral, the judge did the consideration to give the ruling based on the facts are revealed in the trial. In its consideration, the judge can consider both in juridical and non-juridical terms. Bangil District Court judge's ruling against drug abuse cases committed by Dimas Sugiarto dropped imprisonment for 1 (one) year and 8 (eight) months. But actually Dimas Sugiarto can get rehabilitation because he is narcotics abusers. Therefore, what makes the judge's basic consideration in the imposition of prison penalties rather than sanctions in the form of rehabilitation of narcotics abusers for themselves in the decision of Bangil District Court number 408/Pid.Sus/2019/PN.Bil. The purpose of this research is to find out the judge's basic consideration in the imposition of prison penalties rather than sanctions in the form of rehabilitation of narcotics abusers for themselves in the decision of Bangil District Court number 408/Pid.Sus/2019/PN.Bil. The research method used is normative legal research with a research approach in the form of a statute approach and a case approach. Types of legal materials consist of primary legal materials, secondary legal materials, and non-legal materials. The analysis technique of this research used the prescriptive analysis method.